Association between socioeconomic status, surgical treatment and mortality in patients with colorectal cancer. Issue 9 (11th June 2014) - Dik, V. K.; Aarts, M. J.; Van Grevenstein, W. M. U.; Koopman, M.; Van Oijen, M. G. H.; Lemmens, V. E.; Siersema, P. D.
<x xml:space="preserve">Abstract</x> Background High socioeconomic status is associated with better survival in colorectal cancer (CRC). This study investigated whether socioeconomic status is associated with differences in surgical treatment and mortality in patients with CRC. Methods Patients diagnosed with stage I–III CRC between 2005 and 2010 in the Eindhoven Cancer Registry area in the Netherlands were included. Socioeconomic status was determined at a neighbourhood level by combining the mean household income and the mean value of the housing. Results Some 4422 patients with colonic cancer and 2314 with rectal cancer were included. Patients with colonic cancer and high socioeconomic status were operated on with laparotomy (70·7 versus 77·6 per cent; P = 0·017), had laparoscopy converted to laparotomy (15·7 versus 29·5 per cent; P = 0·008) and developed anastomotic leakage or abscess (9·6 versus 12·6 per cent; P = 0·049) less frequently than patients with low socioeconomic status. These differences remained significant after adjustment for patient and tumour characteristics. In rectal cancer, patients with high socioeconomic status were more likely to undergo resection (96·3 versus 93·7 per cent; P = 0·083), but this was not significant in multivariable analysis (odds ratio (OR) 1·44, 95 per cent confidence interval 0·84 to 2·46). The difference in 30‐day postoperative mortality in patients with colonic cancer and high and low socioeconomic status (3·6 versus 6·8 per cent; P < 0·001) was not significant after adjusting for age, co‐morbidities, emergency surgery, and anastomotic leakage or abscess formation (OR 0·90, 0·51 to 1·57). Conclusion Patients with CRC and high socioeconomic status have more favourable surgical treatment characteristics than patients with low socioeconomic status. The lower 30‐day postoperative mortality found in patients with colonic cancer and high socioeconomic status is largely explained by patient and surgical factors.